A methodology to compile multi-hazard interrelationships in a data-scarce setting: an application to the Kathmandu Valley, Nepal - H. E. Thompson; J. C. Gill; R. Šakić Trogrlić; F. E. Taylor; B. D. Malamud (Natural Hazards and Earth System Sciences)
This paper introduces a multifaceted methodology to identify and compile single natural hazards and multi-hazard interrelationships within the context of data-scarce urban settings, exemplified by the Kathmandu Valley, Nepal. This approach integrates (i) five blended types of evidence to support a more nuanced and holistic understanding of a hazardscape where data are scarce and (ii) a 2 h practitioner stakeholder workshop with seven participants to provide greater context to the hazards, consider their impacts through the co-production of multi-hazard interrelationship scenarios, and show how this methodology could support more people-centred disaster risk reduction (DRR) strategies. We use blended evidence types, including academic literature, grey literature, media, databases, and social media, to systematically search for exemplars of single hazard types and multi-hazard interrelationships that have influenced or could potentially influence the Kathmandu Valley. We collated 58 sources of evidence for single hazard types and 21 sources of evidence for multi-hazard interrelationships. Using these sources, our study identified 21 single hazard types across 6 hazard groups (geophysical, hydrological, shallow Earth processes, atmospheric, biophysical, and space/celestial hazards) and 83 multi-hazard interrelationships (12 have direct case study evidence of previous influence in the Kathmandu Valley) that might influence the Kathmandu Valley. These exemplars are collated into a Kathmandu Valley Single Hazards and Multi-Hazard Interrelationships Database (Thompson et al., 2024) accompanying this paper. We supplement these exemplars with multi-hazard interrelationship scenarios and multi-hazard impacts developed by practitioner stakeholders engaged in DRR research and practice in the Kathmandu Valley. The results illustrate the complexity of the hazardscape, with many single hazard types and multi-hazard interrelationships potentially influencing the Kathmandu Valley. The research emphasises the importance of inclusive DRR strategies that recognise disaggregated impacts experienced by different social groups. This knowledge can inform the development of dynamic risk scenarios in planning and civil protection, thus strengthening multi-hazard approaches to DRR in “Global South” urban areas such as the Kathmandu Valley.